Conversion of Neutral Speech into Emotional Speech in Hindi Language based on Supra Segmental Features - Agarwal, Archana; Johri, Prashant (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Speech form is becoming a prevalent and imperative practice as interface between a user and computers systems and smart machines. Mode of input and output in computers and other similar devices in the coming era will be dominated by speech form. To add the spontaneity and intelligibility, emotions play expressive role to ordinary speech. Therefore, it is latest emerging area of research. The practice of converting neutral speech into the intended emotional speech involves examining, identifying, and then changing the characteristics of the speech utterance. The functions of prosodic characteristics, in particular the fundamental frequency F0, pitch, and intensity, are studied for various emotions and employed for emotion conversion. This paper discusses a methodology for conversion of emotions from neutral to Happy, Sad and others for Hindi language speech. The algorithm is developed based using Linear Modification Model where direct modifications are done on F0 contours, pitch and duration on the segmented part of the speech. The continuous speech sentence is segmented into different parts such as words and analysis is done for above said parameters between different emotions of the same neutral speech. Based on the analysis these parameters are modified in the target emotion.